LIBERAL AND PROFESSIONAL STUDIES IN THE UNDERGRADUATE CURRICULUM - Shields, James J. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1969)
The problem of how to strike a happy and reasonable balance between liberal and professional studies in the undergraduate curriculum is a particularly acute one for American academicians who must account to their various publics for the practical and immediate relevance of their programs as well as for their intellectual quality. The rapid expansion of undergraduate teacher programs over the last fifty years has been a major factor in keeping this problem alive and public. So important is teacher education as a symbol of the problem that some institutions, notably Yale University under A. Whitney Griswold, have tried to resolve the issue by severely curtailing teacher education programs. However, there are few for whom the question of professional studies in the undergraduate curriculum is an all-or-nothing issue. For most, the issue involves a consideration of when professional courses should be given, how many should be required, and what kinds are the proper concerns of colleges and universities.